Gender in the planning process - Arnold, Vicky (My University, 2016)
Women and gender have not been adequately considered in development planning and practise. [Abbreviated Abstract. Open document to view full version]
A discourse submitted to the Department of Town and Regional Planning, Faculty of Architecture, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of Science in Development Planning, October 1994
Keywords: Women in development--South Africa; Women--Employment--South Africa